The The Legal Problems of Weakness Supervision of Binary Option in Indonesia: Weakness Supervision of Binary Option in Indonesia - Mafaza, Ahmad Yunan Salsabilla; Kharisma, Dona Budi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
This article aims to find out and assess the forms of binary option supervision in Indonesia contained in statutory regulations. This article discusses the legal problems of the weakness of binary option supervision in Indonesia. This research uses normative research methods using primary and secondary legal materials collected using literature studies with a statutory approach. This study found that although supervision of commodity futures trading in Indonesia has been carried out by Bappebti, there are still problematic weaknesses in supervising binary option trading which is currently a new trend in Indonesian society. Futures trading in Indonesia is regulated in Law No. 10 of 2011 concerning Commodity Futures Trading. Bappebti's supervision has legal problems, namely in the form of the absence of a special regulation on binary option trading, lack of education for the public, imposition of sanctions that are less strict, and the existence of legal vagueness. Bappebti is expected to have a legal strategy in optimizing binary option supervision in Indonesia in the form of: making strict regulations, socializing to the public about the dangers of illegal investment, increasing financial and investment literacy, and can cooperate with foreign regulators to improve binary option supervision in Indonesia.